Exploring the Promise of Flavonoids to Combat Neuropathic Pain: From Molecular Mechanisms to Therapeutic Implications - Uddin, Md. Sahab; Mamun, Abdullah Al; Rahman, Md. Ataur; Kabir, Md. Tanvir; Alkahtani, Saad; Alanazi, Ibtesam S.; Perveen, Asma; Ashraf, Ghulam Md; Bin-Jumah, May N.; Abdel-Daim, Mohamed M. (Frontiers in Neuroscience, 2020)
Neuropathic pain (NP) is the result of the irregular processing in the central or peripheral nervous system, which is generally caused by neuronal injury. The management of NP represents a great challenge owing to its heterogeneous profile and significant undesirable side effect of the frequently prescribed psychoactive agents including benzodiazepines (BDZ). Currently, several established drugs including antidepressants, anticonvulsants, topical lidocaine, and opioids are used to treat NP, but they exert a wide range of adverse effects. To reduce the burden of adverse effects, we need to investigate the alternative therapeutics for the management of NP. Flavonoids are the most common secondary metabolites of plants used in folkloric medicine as tranquilizers, which have been claimed to have a selective affinity to the BDZ binding site. Several studies in animal models have reported that flavonoids can reduce NP. In this paper, we emphasize the potentiality of flavonoids for the management of NP.